Comparison of aqueous ammonia and dilute acid pretreatment of bamboo fractions: Structure properties and enzymatic hydrolysis. (January 2015) - Xin, Donglin; Yang, Zhong; Liu, Feng; Xu, Xueru; Zhang, Junhua
Highlights: Structure and hydrolysability of SAA and DA pretreated bamboo were compared. Different bamboo fractions had different structure properties and hydrolysabilities. SAA was more efficient than DA pretreatment in the hydrolysis of bamboo. Supplementation of xylanase was more effective than increase of cellulases loading. SAA pretreatment with XYL addition was promising method for bamboo bioconversion. Abstract: The effect of two pretreatments methods, aqueous ammonia (SAA) and dilute acid (DA), on the chemical compositions, cellulose crystallinity, morphologic change, and enzymatic hydrolysis of bamboo fractions (bamboo yellow, timber, green, and knot) was compared. Bamboo fractions with SAA pretreatment had better hydrolysability than those with DA pretreatment. High crystallinity index resulted in low hydrolysis yield in the conversion of SAA pretreated bamboo fractions, not DA pretreated fractions. The increase of cellulase loading had modestly positive effect in the hydrolysis of both SAA and DA pretreated bamboo fractions, while supplement of xylanase significantly increased the hydrolysis of the pretreated bamboo fractions, especially after SAA pretreatment. The results indicated that SAA pretreatment was more effective than DA pretreatment in conversion of bamboo fractions, and supplementation of xylanase was necessary in effective conversion of the SAA pretreated fractions into fermentable sugars.